2020
DOI: 10.3390/foods9060701
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Alkaline Treatment on Structural Modifications of Chlorophyll Pigments in NaOH—Treated Table Olives Preserved without Fermentation

Abstract: Alkaline treatment is a key stage in the production of green table olives and its main aim is rapid debittering of the fruit. Its action is complex, with structural changes in both the skin and the pulp, and loss of bioactive components in addition to the bitter glycoside oleuropein. One of the components seriously affected are chlorophylls, which are located mainly in the skin of the fresh fruit. Chlorophyll pigments are responsible for the highly-valued green color typical of table olive specialties not pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Alkali treatment and subsequence washing, and soaking, has been reported as an efficient method to debitter OPs (Yıldız Turgut et al ., 2016). Also, similar treatments have been used for debittering olives, showing a loss of bioactive compounds such as phenolic compounds (TPC) when compared to fresh olives (Alexandraki et al ., 2014; Berlanga‐Del Pozo et al ., 2020). Results of the present study seemed to confirm the utility of alkali blanching to decrease TPC as well as bitterness perception in OP, although the other methods seemed to lead to a greater decrease in TFC (e.g., salt blanching or lactic acid fermentation).…”
Section: Discussionmentioning
confidence: 99%
“…Alkali treatment and subsequence washing, and soaking, has been reported as an efficient method to debitter OPs (Yıldız Turgut et al ., 2016). Also, similar treatments have been used for debittering olives, showing a loss of bioactive compounds such as phenolic compounds (TPC) when compared to fresh olives (Alexandraki et al ., 2014; Berlanga‐Del Pozo et al ., 2020). Results of the present study seemed to confirm the utility of alkali blanching to decrease TPC as well as bitterness perception in OP, although the other methods seemed to lead to a greater decrease in TFC (e.g., salt blanching or lactic acid fermentation).…”
Section: Discussionmentioning
confidence: 99%
“…Hynninen and Hyvärinen further demonstrated the allomerization pathways of chlorophylls under essentially anhydrous chlorophyll and thoroughly dried methanol [150]. The treatment of 2-5% NaOH from 7 to 4 h increased the formation of allomerized derivatives of chlorophyll [149,152,153]. Some examples of chlorophyllides purification by chromatography are shown in Table 4.…”
Section: Purification Using Chromatographymentioning
confidence: 96%
“…At the chiral C13 2 -position, chlorophyll(ide)s are transformed to epimers via stereoinversion and allomers via oxidation [146][147][148]. It is well known that the epimerization and allomerization occur easily under basic conditions and an alcoholic solution [149,150]. Hynninen et al reported a free-radical allomerization mechanism of chlorophyll [151].…”
Section: Purification Using Chromatographymentioning
confidence: 99%
“…However, its action is complex and structural changes in the olive, and loss of bioactive components, also occur. Because chlorophylls are one of the bioactive components seriously affected, Berlanga-Del Pozo et al [ 10 ] designed a work aimed to investigate the effect of the alkaline treatment on these pigments that are responsible for the characteristic bright green color of table olives not preserved by fermentation. Specifically, the authors investigated the effect of nine combinations of two important parameters of the alkali treatment (NaOH concentration and treatment time) on green table olives processed in the Campo Real style and preserved for 1 year under refrigerated conditions.…”
mentioning
confidence: 99%
“…To conclude, the present special issue consists of 10 original research papers and two review articles. The research papers, focused on recent research advances related to characterization and processing of table olives, have covered microbiological and chemical changes in table olives during spontaneous or controlled fermentation employing different cultivars [ 3 ], characterization of their composition of volatiles and the sensory profile [ 5 , 6 , 7 ], mineral composition [ 8 ] and bioavailability [ 9 ], changes in bioactive components (chlorophylls) by processing [ 10 ], optimized use of starter cultures for the improvement of the different fermentative processes [ 4 , 5 ], and new strategies to reduce sodium and additives, to stabilize the organoleptic properties and avoid defects [ 11 , 12 ].…”
mentioning
confidence: 99%